Per una rilettura dell'art. 79 del codice del Terzo Settore (Società e diritti, 2024)
In this contribution the author raises the question whether the ETS is a commercial entity or not. Art. 79 of the CTS is focused around two fundamental points: to establish the nature of the activity of general interest and to establish the nature of the entity of the Third Sector.